Assessing EU energy resilience and vulnerabilities: Concepts, empirical evidence and policy strategies - Dario Guarascio; Jelena Reljic; Francesco Zezza (Austrian Foundation for Development Research (ÖFSE), 2024)
This paper analyses energy vulnerability and resilience in the EU. First, a comprehensive review of the relevant literature is carried out, discussing key concepts and indicators used to assess countries' relative positioning vis-à-vis energy shocks. Second, we rely on a large set of indicators (i.e., share of energy intensive industries, import dependency and market concentration, productive and technological capabilities in the renewables domain, policy efforts to increase energy resilience) to provide a thorough mapping of the EU Member States positioning in terms of energy vulnerability and resilience. Third, we assess industrial and energy policy actions put in place at both the EU and the national level, highlighting relevant heterogeneities and discussing whether policy efforts are consistent with the degree of vulnerability of Member States.
Keywords: 330; Energy vulnerability; resilience; Europe; industrial policy